Facile biomimetic synthesis of AgNPs using aqueous extract of Helichrysum arenarium: characterization and antimicrobial activity - Yilmaz, Mustafa Tahsin; Ispirli, Humeyra; Taylan, Osman; Balubaid, Mohammad; Dertli, Enes (TAYLOR & FRANCIS INC, 2022)
The present study focuses on synthesis of silver nanoparticles (AgNPs) by employment of a green and facile synthesis method. Aqueous extract of Helichrysum arenarium was used as a reducing and capping agent. The bioreduction of silver particles was monitored using UV-Vis spectroscopy based on increase in color intensity led by surface plasmon resonance. SEM, TEM, FTIR, DSC, and XRD analyses were followed for characterization, divulging that the nanoparticles were thermally resistant in the size of approximately 20 nm with a quasi-spherical shape without any agglomeration. AgNPs possessed a nanocrystal form with presence of crystalline Ag. EDAX analysis was used to verify that the nanoparticles were silver as revealed by a typical optical absorption peak of metallic silver nanocrystallites. The AgNPs were shown to have strong antibacterial and antifungal effects on some foodborne pathogens. The method developed in this study could offer a green, facile biomimetic, and cost-effective method.
Keywords: Facile biomimetic synthesis; extract of Helichrysum arenarium; silver nanoparticles; structural and thermal characterization; antimicrobial activity; ZINC-OXIDE NANOPARTICLES; GREEN SYNTHESIS; LEAF EXTRACT; GOLD NANOPARTICLES; ANTIBACTERIAL ACTIVITY; BIOSYNTHESIS; ANTIOXIDANT; LINN.; NANOMATERIALS; Chemistry; Science & Technology - Other Topics